2014
DOI: 10.1099/ijs.0.060988-0
|View full text |Cite
|
Sign up to set email alerts
|

Oribacterium parvum sp. nov. and Oribacterium asaccharolyticum sp. nov., obligately anaerobic bacteria from the human oral cavity, and emended description of the genus Oribacterium

Abstract: Three strictly anaerobic, Gram-positive, non-spore-forming, rod-shaped, motile bacteria, designated strains ACB1 T , ACB7 T and ACB8, were isolated from human subgingival dental plaque. All strains required yeast extract for growth. Strains ACB1 T and ACB8 were able to grow on glucose, lactose, maltose, maltodextrin and raffinose; strain ACB7 T grew weakly on sucrose only. The growth temperature range was 30-42 6C with optimum growth at 37 6C. Major metabolic fermentation end products of strain ACB1 T were ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 22 publications
1
16
0
1
Order By: Relevance
“…In agreement, decreased Lachnospiraceae were previously described in oral microbiome from obese compared to non-obese type 2 diabetic individuals [40]. Characterization of Stomatobaculum and Oribacterium asaccharolyticum, highlighted that Stomatobaculum encoded in its genome the cysteine desulfurase gene [41], whereas the major metabolic end product of Oribacterium asaccharolyticum was acetate [42]. Interestingly, a recent study evaluated the associations of BMI with circulating microbiota biomarkers in African American men and found that propionic and butyric SCFAs, but not acetic acid, were significant positive predictors of BMI [43].…”
Section: Discussionsupporting
confidence: 78%
“…In agreement, decreased Lachnospiraceae were previously described in oral microbiome from obese compared to non-obese type 2 diabetic individuals [40]. Characterization of Stomatobaculum and Oribacterium asaccharolyticum, highlighted that Stomatobaculum encoded in its genome the cysteine desulfurase gene [41], whereas the major metabolic end product of Oribacterium asaccharolyticum was acetate [42]. Interestingly, a recent study evaluated the associations of BMI with circulating microbiota biomarkers in African American men and found that propionic and butyric SCFAs, but not acetic acid, were significant positive predictors of BMI [43].…”
Section: Discussionsupporting
confidence: 78%
“…In addition, we identified several taxa not previously reported to occur at PI sites, including O. asaccharolyticum , V. dispar, G. elegans , and C. durum , that is, natural inhabitants of the human aerodigestive tract (Chen et al., ; Kumar et al., ; Ohara‐Nemoto et al., ; Sizova et al., ).…”
Section: Discussionmentioning
confidence: 84%
“…There are very few studies that make reference to it in terms of health and disease, but there is one record of Oribacterium being enriched in saliva samples from healthy control subjects compared to saliva from patients with oral squamous cell carcinoma [35]. The major fermentation end product of two of the three species in this genus, which were both found in our dataset, O. parvum and O. sinus, is lactate [34,36]. Lactate levels in the saliva could control viral titers once reactivation occurs, as physiological levels of lactic acid present in the vaginal tract have shown potency in HIV and Chlamydia inactivation [37,38].…”
Section: Viral Reactivationmentioning
confidence: 91%
“…Members of the genus Oribacterium are non-spore forming, gram positive, motile, and strict anaerobes that have been isolated from human subgingival plaque [34]. There are very few studies that make reference to it in terms of health and disease, but there is one record of Oribacterium being enriched in saliva samples from healthy control subjects compared to saliva from patients with oral squamous cell carcinoma [35].…”
Section: Viral Reactivationmentioning
confidence: 99%